FOR AND AGAINST MORAL CONVERSATION-STOPPERS. Issue 50 (27th September 2018) - Piper, Mark
Abstract : In this article I argue that although Daniel Dennett is right to hold that moral conversation-stoppers (considerations that tend to bring moral deliberation to an end) are practically helpful, there are also moral and philosophical benefits to be gained from developing a habit of being suspicious of them.